Associations of socioeconomic status with prevalence, awareness, treatment, and control of hypertension in a general Japanese population: NIPPON DATA2010. Issue 2 (February 2017) - Satoh, Atsushi; Arima, Hisatomi; Ohkubo, Takayoshi; Nishi, Nobuo; Okuda, Nagako; Ae, Ryusuke; Inoue, Mariko; Kurita, Shuji; Murakami, Keiko; Kadota, Aya; Fujiyoshi, Akira; Sakata, Kiyomi; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To investigate associations between socioeconomic status (SES) and prevalence, awareness, treatment, and control of hypertension in Japan's general population. Methods: In 2010, we established a cohort of participants in the National Health and Nutrition Survey of Japan. The cohort included 2623 adults from 300 randomly selected areas across Japan. Using baseline data, four cross-sectional analyses were performed: association of SES with prevalent hypertension in 2623 participants; association of SES with unawareness of hypertension and with no treatment in 1282 hypertensive patients; and association of SES with uncontrolled hypertension in 720 treated hypertensive patients. SES was classified according to employment status, length of education, marital and living status, and household expenditure. Results: The overall prevalence of hypertension was 48.9%. Among hypertensive participants, the proportions of unawareness and no treatment were 33.1 and 43.8%, respectively. Target blood pressure levels were not achieved among 61.2% of treated hypertensive patients. Hypertension was more prevalent in the unmarried and living alone group than in the married group (odds ratio 1.76; 95% confidence interval 1.26–2.44), after adjustment for age, sex, BMI, smoking, alcohol consumption, habitual exercise, history of cardiovascular diseases, diabetes mellitus, hypercholesterolemia, dietary sodium, and potassium intake. SES was not clearly associated with unawareness, no treatment, nor poor control of hypertension. Conclusion: Being unmarried and living alone was associated with increased prevalence of hypertension. There was no clear association of SES with unaware, untreated, and uncontrolled hypertension.